The effectiveness of nurse resources utilization in health services in Belarus - Piecewicz-Szczęsna, Halina; Matwiejczyk, Tatiana; Walczuk, Edward (Nursing Problems / Problemy Pielęgniarstwa, 2009)
Introduction. Providing adequate number of employees and correct distribution of human resources are essential conditions of achieving proper organizational system effectiveness. According to the World Health Organization experts opinions the problem of insufficient number of nurses can’t be solved only by means of increment in number of employed ones. It requires the reorganization of nurses working time and working conditions, too. Aim. The aim of this work was to evaluate management’s efficacy in regard to the taking advantage of existing nurse resources in hospitals in Belarus. Material and methods. The study was performed in three municipal hospitals in Belarus. By the help of medical documentation as well as sample observations results analyses there were estimated the real levels of exploitations of nominal as well as flexible nurses working time in selected departments of mentioned hospitals. Results and conclusions. The results showed that nursing care quality level in Belarus was worse than possible. The nominal working time was not fully utilized. There were observed some undesired aspects in the structure of nurse’s working time. The unsatisfactory level of working time exploitation was caused by insufficient flexible time utilization. Nurses spent too much time for performing activities other than their professional duties, such as those concerning coordination and organization of their work (35.96%). Meanwhile, the ratio of the time set aside for direct nursing activities realization was too low (23.63% of all the time of their professional activities). The obtained data allow the authors to conclude that the existing nurse resources in inpatient care units in Belarus are not utilized in the effective way.